McGraduates or globo sapiensi? - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
Faced with global environmental and financial crises, even the World Economic Forum (WEF) (2008: 5) has called for a “fundamental reboot” to create new, sustainable systems, including education.